Aldosterone synthase inhibitors in uncontrolled and resistant hypertension: A phenotype-stratified systematic review and network meta-analysis of randomized trials - Ismaila Ajayi Yusuf; Olurotimi J. Badero; Alozie Ihesiulo; Micah Nnabuko Okwah; Abieyuwa Oshodin; Emmanuella Asikong (PLoS ONE, 2026)
Background Aldosterone synthase inhibitors (ASIs) have emerged as a mechanistically targeted strategy for resistant and uncontrolled hypertension; however, no head-to-head trials exist, and comparative efficacy and safety remain uncertain. We compared their efficacy and safety using network and pairwise meta-analysis of randomized trials. Methods This systematic review and meta-analysis adhered to the PRISMA guidelines. PubMed/MEDLINE, Scopus, Embase, ClinicalTrials.gov, and Cochrane Library were searched from inception to January 14, 2026, for randomized trials evaluating ASIs versus placebo or standard care. A frequentist random-effects network meta-analysis assessed systolic (SBP) and diastolic blood pressure (DBP). Dichotomous safety outcomes were pooled using Hartung–Knapp random-effects models. Network consistency was evaluated using design-by-treatment interaction modeling. Prespecified subgroup analyses stratified outcomes by hypertension phenotype (resistant vs uncontrolled). Results Across 7 RCTs (n = 2,828), all ASIs significantly reduced SBP versus placebo: baxdrostat −8.63 mmHg (95% CI −10.84 to −6.42), lorundrostat −7.47 mmHg (95% CI −9.54 to −5.40), and LCI699/osilodrostat −5.63 mmHg (95% CI −9.15 to −2.12), with no significant indirect differences between agents. In resistant hypertension, lorundrostat (−9.00 mmHg; 95% CI −13.19 to −4.81) and baxdrostat (−8.77 mmHg; 95% CI −10.50 to −7.05) demonstrated pronounced reductions. In uncontrolled hypertension, LCI699/osilodrostat showed the largest point estimate (−10.55 mmHg; 95% CI −16.49 to −4.61), though this derives from a single early-phase trial and requires cautious interpretation. DBP reductions were significant for baxdrostat (−3.23 mmHg; 95% CI −4.73 to −1.73) and lorundrostat (−3.60 mmHg; 95% CI −5.43 to −1.77). Hypotension (RR 2.67), hyperkalemia (RR 7.94), and hyponatremia (RR 2.07) were significantly increased; serious adverse events, discontinuation, and network inconsistency were not detected. Conclusions ASIs provide clinically meaningful BP reduction across both hypertension phenotypes; however, short-term use is associated with hypotension and electrolyte disturbances, necessitating careful monitoring. Phenotype-specific efficacy and long-term safety require validation in outcome-driven trials. Systematic Review Registration: PROSPERO CRD420251266257